Neuroradiological findings in children with subdural hematoma and suspected abusive head trauma - Sverre Morten Zahl; Jacob Andersson; Knut Wester; Johan Wikström (Wiley, 2023)
Abstract Aim Abusive head trauma (AHT) is often suspected in infants with subdural hematoma (SDH). Other neuroradiological findings have also been reported in assumed AHT, such as hypoxic-ischemic injury (HII), cortical vein thrombosis, and subarachnoid hemorrhage. The purpose of this study was to investigate neuroradiological and clinical findings in cases of suspected AHT. Methods Infants with SDH suspected to be caused by AHT, referred to the Swedish National Board of Forensic Medicine during the period 1994-2018, were considered for inclusion. Results Ninety‐six cases were included, with 68% males. The proportions of infants born prematurely, and twins, were higher than in the normal population. Signs of "benign enlargement of the subarachnoid space" (BESS) were found in 36% and were associated with chronic SDH and nonacute symptoms. HII was found in 16% and was associated with subarachnoid hemorrhage and high mortality, but not traumatic findings. Clinical signs of increased intracranial pressure were associated with retinal hemorrhages. Conclusion This analysis indicates that infants with SDH investigated for AHT are a heterogeneous group with some cases associated with external signs of trauma and others with possibly nontraumatic etiologies. Infants with BESS are more likely to have chronic SDH and nonacute symptoms. Patients with HII often have serious/fatal outcomes, but are not associated with external signs of injury. The overrepresentation of males, premature infants, and twins is unexplained.